PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK YANG DIMODERASI OLEH INTENSITAS PEMERIKSAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KUNINGAN - Dadang Suhendar, Ida Soraya (Program Studi Akuntansi, Universitas Kuningan, 2015)
The purpose of this study was to illustrate the level of taxpayer compliance, the tax audit intensity, and the tax revenue as well as the influence of taxpayer compliance and tax audit intensity either simultaneously or partially on tax revenue, and the influence of the tax audit intensity of the interaction level of taxpayer compliance on tax revenue in the Tax Office Primary Kuningan. The hypothesis that the authors propose was the level of taxpayer compliance and tax audit intensity simultaneously affect the tax revenue, the level of taxpayer compliance a positive effect on tax revenue, tax audit intensity positive effect on tax revenue, tax audit intensity positive effect on the interaction level of taxpayer compliance on tax revenue.Ã‚Â This research was conducted by using descriptive method verifikatif with quantitative approach. The study population was taxpayer compliance data, the realization of tax audits, and tax revenue to the Tax Office Primary Kuningan. Sampling using non probability sampling was purposive sampling technique in order to obtain samples of the data that taxpayer compliance, realization of tax audits, and tax revenue to the Tax Office Primary Kuningan for 5 years was from the year 2009 until the year 2013 in the form of data analysis tools description and analysis of statistical analysis through regression analysis moderating.Ã‚Â Based on the results of the descriptive analysis showed that the Tax Office Primary Kuningan generally have high levels of tax compliance, tax audit intensity, and tax revenues were likely to increase each semester with an average of 15583.50 respectively SPT, 16017.4010 tens of millions of dollars, and 59.8960 tens of millions of dollars. Statistical analysis showed that the level of taxpayer compliance and tax audit intensity simultaneously and significantly influential to tax revenues, the level of taxpayer compliance was significantly positive effect on the increase in tax revenue, tax audit intensity was significantly positive effect on tax revenue, and the tax audit intensity significantly positive effect on the interaction level of taxpayer compliance on tax revenues.